Bicycle Transport-An Original Solution for Building Cycle Paths on Unused Railway Tracks - Šooš, Lubomír; Zich, Miloš; Čačko, Viliam; Kuznietsov, Yurii; Chlebo, Ondrej; Schevchenko, Oleksandr; Švaříčková, Ivana (University North, 2025)
The issue of functional cycle paths is a long-term pressing problem in Slovakia. Cycling combines many benefits that are related to a healthy lifestyle, an environmental approach to transport and, last but not least, the development of the given region. Construction of modular cycle paths on unused railway tracks is one of the possible and modern approaches. The total length of long-term unused railway tracks in Slovakia is approximately 180-220 kilometers. This approach offers several benefits, such as the meaningful use of unused tracks, addressing legal aspects of land use, recycling of unusable waste, or the possibility of quick restoration of the original railroad track. The aim of this article is to present an innovative project for building cycle paths on unused railway lines with the meaningful use of plastic and rubber waste.

The issue of functional cycle paths is a long-term pressing problem in Slovakia. Cycling combines many benefits that are related to a healthy lifestyle, an environmental approach to transport and, last but not least, the development of the given region. Construction of modular cycle paths on unused railway tracks is one of the possible and modern approaches. The total length of long-term unused railway tracks in Slovakia is approximately 180-220 kilometers. This approach offers several benefits, such as the meaningful use of unused tracks, addressing legal aspects of land use, recycling of unusable waste, or the possibility of quick restoration of the original railroad track. The aim of this article is to present an innovative project for building cycle paths on unused railway lines with the meaningful use of plastic and rubber waste.
Bicycle Transport-An Original Solution for Building Cycle Paths on Unused Railway Tracks
Keywords: bicycle transport; modular; original patent solution; prefabricated panels; railway tracks; removable system; bicycle transport; modular; original patent solution; prefabricated panels; railway tracks; removable system